2011
DOI: 10.1590/s1806-83242011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the association between simvastatin and demineralized bovine bone matrix on bone repair in rats

Abstract: Simvastatin, a drug used to lower blood cholesterol, has been reported to have an anabolic effect on bone. The purpose of this study was to evaluate the influence of simvastatin and demineralized bovine bone matrix (DBBM) on the repair of rat calvarial defects. Defects of 5 mm were created in 64 rats, divided into four groups: no local treatment (control); treatment with DBBM (DBBM); treatment with a combination of simvastatin solution (2.2 mg/50 µl) and DBBM (DBBMSIM-1); and treatment with simvastatin solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…51 demonstrated controversial, and even negative, effects of statins on bone repair, the vast majority of the studies in Table 1 support the beneficial role of this group of drugs. The administration of statins presents anabolic effects by promoting osteoblast activity and suppressing osteoclasts.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…51 demonstrated controversial, and even negative, effects of statins on bone repair, the vast majority of the studies in Table 1 support the beneficial role of this group of drugs. The administration of statins presents anabolic effects by promoting osteoblast activity and suppressing osteoclasts.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…25,35,38 It has been shown that low dose of Simvastatin (0.5 mg) reduces bone density on day 30 while after 60 days of injury, regardless of the dose, Simvastatin both at 0.5 and 2.2 mg/rat BW retards bone healing. 58 In rabbits, 2.5 and 5 mg Simvastatin/scaffold or/rabbit BW were the most effective doses responsible for bone regeneration. 38,92 In mice, 0.6 to 1 lmol/L and also 2.2 mg/scaffold or/mouse BW were effective in bone healing.…”
Section: Dosementioning
confidence: 97%
“…Impregnation of bone scaffolds with Simvastatin is the simplest way, but because the drug has high delivery rate (burst release effect) in the injured area, most of the drug is dissolved in the blood circulation and removed from the body so that the bioavailability of the drug is too short to be effective in influencing the reparative and remodelling phase of bone healing. 58,60 Alternatively, Simvastatin can be coated on the bone scaffolds by various methods such as spray techniques and ultrasonic dispersion. 1,113 However, in this method only low concentrations of Simvastatin can be coated and thus, the drug availability is more valuable in the inflammatory phase of bone healing and cannot be increased in order to influence later stages (e.g.…”
Section: Drug Delivery Systems Used In Simvastatin Therapymentioning
confidence: 99%
“…Some authors did not observe new bone formation induced by simvastatin [22][23][24] . Other reports indicate that simvastatin 17,[25][26][27][28] influenced and stimulated new bone formation.…”
Section: Immunohistochemistry Evaluationmentioning
confidence: 99%